Teacher and Pupil: Happiness of Interaction - O. A. Donskikh; L. Yu. Logunova (Высшее образование в России)
Happiness is a universal category that describes processes of human existence. Getting education, acquiring knowledge is an important process of personal and civic development. The research problem posed in the article: is it possible to feel happiness and pleasure during the process of learning? The authors analyze this problem from the theoretical positions of philosophy, axiology, and sociology of culture. Overview of the theories and techniques of happiness reveals the methodical helplessness and invalidity of Humanities in relation to the research of happiness as a natural right of a man. The authors believe that the formulation and justification of the category of “feeling”, and its introduction into the scientific terminology of social studies and Humanities are in demand in modern scientific practice. Modern pedagogical practice, which is limited by standards and instructions, is far from being a happy process of acquiring knowledge and self-disclosure by a student and a teacher. It does not only involve the release of feelings, but also poses threat to the social order by violating the social position of the status of the “teacher – student” interaction, “freezing” the meanings of the process of social inheritance due to the requirements of conformity with performance indicators, thus transferring the educational process from the domain of culture onto the plane of market relations. Value of knowledge is included into the axiological system of society and does not need to be evaluated. To realize the value potential of knowledge means to create conditions for happy interaction of the main participants of this process – the carriers of the “teacher” and “pupil” statuses, but not to control the amount of this process. Knowledge may have terminal and instrumental meanings, but its main purpose is to serve the formation of personality, and not to serve the existence and needs of controllers.